2016
DOI: 10.1016/j.paid.2016.04.067
|View full text |Cite
|
Sign up to set email alerts
|

The role of attachment style and anthropomorphism in predicting hoarding behaviours in a non-clinical sample

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…Interestingly, a previous study found that, among individuals with OCD, women had significantly higher levels of interpersonal attachment insecurity [40], and another study of a non-clinical sample found that women had significantly higher scores on hoarding severity, attachment difficulties, and anthropomorphism [44]. There also is other evidence that the etiology of hoarding may be different in women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a previous study found that, among individuals with OCD, women had significantly higher levels of interpersonal attachment insecurity [40], and another study of a non-clinical sample found that women had significantly higher scores on hoarding severity, attachment difficulties, and anthropomorphism [44]. There also is other evidence that the etiology of hoarding may be different in women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Defined as "perceiving humanlike characteristics in either real or imagined nonhuman agents" (Epley, Waytz, Akalis, & Cacioppo, 2008, p. 144), anthropomorphism is a common phenomenon that many people experience to varying degrees. To date, a few studies have reported significant positive associations between anthropomorphism and hoarding symptoms (Neave, Jackson, Saxton, & Hönekopp, 2015;Neave, Tyson, McInnes, & Hamilton, 2016;Norberg, Crone, Kwok, & Grisham, 2018;Timpano & Shaw, 2013). Timpano and Shaw (2013) also showed that anthropomorphism increased the strength of association between hoarding beliefs and emotional attachment to novel items.…”
Section: Anthropomorphism and Possessions As Self-extensionsmentioning
confidence: 99%
“…The aim of this study is to extend the cognitive-behavioral therapy model of hoarding by elaborating on the role that object attachment plays in hoarding symptoms. Aspects of object attachment identified include the tendency to look into possessions for comfort and safety (Frost et al, 1995;Hartl et al, 2005), IOA (Nedelisky & Steele, 2009), anthropomorphism (Neave et al, 2016;Timpano & Shaw, 2013), the use of possessions as self-extensions (Dozier et al, 2017), and the use of possessions for the preservation of autobiographical memories (Cherrier & Ponnor, 2010). These facets are, however, not unique to individuals who hoard and therefore one or more of them may not be significantly associated with hoarding symptoms.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…These patterns of behaviour were noted in early studies of hoarding and integrated into the cognitive‐behavioural model of HD (Frost & Hartl, ; Frost & Steketee, ). Yet, whilst emotional attachment has been shown to be an important symptom correlate (Kyrios et al ., ; Neave, Tyson, McInnes, & Hamilton, ) and mediator of treatment (Levy et al ., ), it remains an under‐researched component of the model.…”
Section: Introductionmentioning
confidence: 99%
“…Neave et al . () recruited a community sample ( N = 283) to investigate the association between attachment style and attachment to objects in HD. They found significant positive correlations between attachment to inanimate objects and anxious ( r = .37) as well as avoidant ( r = .27) attachment styles.…”
Section: Introductionmentioning
confidence: 99%